Russia in Africa : resurgent great power or bellicose pretender? - Ramani, Samuel (London : Hurst & Company, 2023)
This book presents a chronological examination of Russia’s post-Cold War foreign policy towards Africa, and outlines the factors that have enabled and impeded the growth of its influence. It pays special attention to the non-material factors behind this rising power; the domestic drivers of Russian decision-making; Moscow’s relationships with fellow external powers; and African perspectives on Russia’s geopolitical role. Samuel Ramani’s analysis cites extensively both Russian-language media and academic sources, and his own interviews with Russian and African elites. His fascinating study challenges popular depictions of Russia as an opportunistic anti-Western actor, instead emphasising Moscow’s strategic commitment to Africa and the endurance of historical memory.
Includes bibliographical references and index.
Keywords: Diplomatic relations; Russia (Federation) -- Foreign relations -- Africa; Africa -- Foreign relations -- Russia (Federation); Afrique -- Relations extérieures -- Russie; Africa; Russia (Federation)